Contrastive view of abbreviations and acronyms and their development - Nedomlel, Roman (Univerzita Pardubice, 2011)
This bachelor's paper deals with word formations which result in the shorter form of the original, source word(s). Namely, there processes are acronyming, abbreviating, blending, clipping and back-forming. In the theoretical part of this bachelor's paper all the necessary terms will be explained via the theories of certain linguists, like Crystal, Brown, Yule, Akmajian, Štekauer, etc. The theoretical part will provide enough information for the research itself. The goal of the research is to prove or disprove theories whether there is a rising tendency in usage of the abbreviations, blends, clips, acronyms and back-formations. The research will be done via the archives of well-known periodicals, namely The New York Times from the USA, The Sunday Times from England and Mladá Fronta Dnes from the Czech Republic. The results of this analysis should determine whether the certain theories are correct and which language uses these shorter forms of the words more frequently.
Kontrastivní pohled na zkratky a zkratková slova a jejich vývoj
Keywords: tvoření slov; zkratky; zkratková slova; zkráceniny; word-formations; abbreviations; acronyms; blends; clips; back-formation